EXPERIMENTAL STUDY ON SHEAR STRENGTHENING OF RC T-BEAMS WITH WEB OPENINGS USING FRP COMPOSITES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Sudden fall of reinforced concrete is may be knows as catastrophic and as the name suggest it is catastrophic, that simply means that it is sudden in nature. No any intimation or no cracks are seen in reinforced concrete. On many old constructions it is found that there is significant damage has been occurred and they need a rework for strengthening. Conventional strengthening methods used for strengthening of shear e.g. post tensioning, enlargement of member along with internal transverse steel, and bonded[1] steel plates are very much cost. Moreover this method requires an extensive manpower, modern equipment, significant time and involvement of much labor. This study was carried out keeping in mind the shear performance and different catastrophic failure modes of RC- T beams modified with bonded GFRP sheets.